The Correlation between Reading Comprehension Ability and Students' English Learning Outcomes - Asriani, Asriani; Atmowardoyo, Haryanto; Talib, Ahmad (Journal of Excellence in English Language Education, 2026)
This study is a type of correlational research that aims to determine the correlation between reading comprehension ability and students' English learning outcomes. The population in this study was all students of class VIII of SMPN 26 Makassar, with the number of samples of this study being 32 students. The data collection technique for this study was using tests and documentation as research instruments. The data analysis technique used in this study was descriptive statistical analysis and inferential statistical analysis. Based on the data analysis, the results of the study were reading comprehension ability with a percentage of 62% in the good category and English learning outcomes with a percentage of 82% in the excellent category. The results of the inferential statistical analysis obtained r_count of 0.525 with a significance of 5% and r_table of 0.361, so that r_count (0.525) > r_table (0.361). Thus, H0 is rejected and H1 is accepted; it can be concluded that there is a significant correlation between reading comprehension ability and students' English learning outcomes.